PRACTICE AND EXPLORATION OF THE ATMOSPHERE CONSTRUCTION OF DIGITAL MEDIA - Yang, Huansong; Zhang, YouYou (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the booming development of the digital media industry, the demand for related professionals is growing. As the cradle of talent training, the construction of digital media laboratory atmosphere plays a crucial role in the cultivation of students' professional skills and innovative ability. Taking the Digital Media Laboratory of Hangzhou Normal University as a case, this paper elaborates how to improve and enhance the learning atmosphere of the laboratory through multi-dimensional means such as the optimization of hardware facilities, the enrichment of teaching resources, the interaction and communication between teachers and students, and the cooperation between schools and enterprises. At the same time, through practice and exploration, this paper puts forward some suggestions on the construction of digital media professional laboratory atmosphere, which aims to provide reference for the construction of similar laboratories in other universities.